2000
DOI: 10.1080/10408440091159176
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Endocrine-Disrupting Chemicals on Wildlife, with Special Reference to the European Situation

Abstract: Many wildlife species may be exposed to biologically active concentrations of endocrine-disrupting chemicals. There is strong evidence obtained from laboratory studies showing the potential of several environmental chemicals to cause endocrine disruption at environmentally realistic exposure levels. In wildlife populations, associations have been reported between reproductive and developmental effects and endocrine-disrupting chemicals. In the aquatic environment, effects have been observed in mammals, birds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
303
0
14

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 717 publications
(321 citation statements)
references
References 44 publications
4
303
0
14
Order By: Relevance
“…In mammals, high levels of TBT have been shown to alter the functions of a variety of endocrine tissues such as the pituitary, endocrine pancreas, gonads and thyroid glands [8,35,44]. We therefore examined the number and morphology of Leydig cells in testes of control fetuses and those exposed to TBT.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, high levels of TBT have been shown to alter the functions of a variety of endocrine tissues such as the pituitary, endocrine pancreas, gonads and thyroid glands [8,35,44]. We therefore examined the number and morphology of Leydig cells in testes of control fetuses and those exposed to TBT.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies with sediments and sewage treatment plant effluents have revealed differential effects when using a combination of different bioassays that capture estrogenic, steroidogenic, dioxin-like, mutagenic/genotoxic and teratogenic effects, fractionation, and chemical analysis, demonstrating the necessity of holistic screening approaches. Also, there are increasing concerns about emerging contaminants including endocrine disrupting chemicals Vos et al 2000), perfluorinated compounds (Giesy and Kannan 2002;Jernbro et al 2007), as well as polybrominated and mixed halogenated dibenzop-dioxins and -furans (Olsman et al 2007a). For these compounds, no or only a limited number of sufficiently specific bioassays are available, and thus, such exposures often cannot be appropriately addressed.…”
Section: Effect Directed Analysesmentioning
confidence: 99%
“…There exist a number of nuclear hormone receptors such as the ER, androgen receptor (AR), thyroid receptor (TR), retinoic acid receptor (RAR), and vitamin D receptor (VDR), which mediate the actions of hormones and vitamins to affect processes from reproduction to development and even general metabolism (8). Thus, environmental pollutants binding to a wide variety of nuclear hormone receptors could induce adverse effects in wildlife (9), as exemplified by a recent study that organotins caused imposex in gastropods through the involvement of retinoid X receptors (RXRs) (10).…”
Section: Introductionmentioning
confidence: 99%